2009
DOI: 10.1149/1.3091903
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nickel on the Local Corrosion Behavior of Amorphous Al-Cu-Mg Based Alloys

Abstract: The effect of a minor amount of Ni on local corrosion behavior was investigated using Al-Cu-Mg amorphous alloys. Cyclic polarization studies revealed that the addition of a small amount of Ni can enhance both pitting and repassivation potentials significantly, in both the amorphous and devitrified crystalline state. The pit growth kinetics were also ennobled and slowed by the minor solute Ni. Electron microscopy analysis revealed a porous layer depleted with Al and Mg in pits, indicating preferential dissoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous reports by the authors regarding the corrosion behavior of these amorphous alloys disclosed the enhanced corrosion resistance due to the addition of Ni as a minor solute element. 32,33 The synthesis of nanoporous Cu via dealloying of the same alloy systems has also been reported. 34 However, the roles of such minor alloying element in corrosion have not yet been elucidated.…”
mentioning
confidence: 97%
“…Previous reports by the authors regarding the corrosion behavior of these amorphous alloys disclosed the enhanced corrosion resistance due to the addition of Ni as a minor solute element. 32,33 The synthesis of nanoporous Cu via dealloying of the same alloy systems has also been reported. 34 However, the roles of such minor alloying element in corrosion have not yet been elucidated.…”
mentioning
confidence: 97%
“…Two types of Al-Cu-Mg-based soluterich amorphous alloys ((Al 75 Cu 17 Mg 8 ) 97 Ni 3 and Al 70 Cu 18 Mg 12 , at%) have recently been discovered that meet this criteria with respect to Ni [2,3]. These alloys provide a rare opportunity to study the role of minor alloying elements on corrosion.Recent investigations revealed that the localized corrosion mode of the solute-rich Al-Cu-Mg-based amorphous alloys was by pitting with localized dealloying of Al and Mg isolated inside of pits [4]. Oxide breakdown…”
mentioning
confidence: 99%
“…Recent investigations revealed that the localized corrosion mode of the solute-rich Al-Cu-Mg-based amorphous alloys was by pitting with localized dealloying of Al and Mg isolated inside of pits [4]. Oxide breakdown…”
mentioning
confidence: 99%
“…X-ray diffraction (XRD), Extended X-ray absorption fine structure (EXAFS), and Scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS) were employed to determine the atomic structure, morphology and compositional distribution pre-and post-corrosion specimens of the amorphous alloys. The post-corrosion specimens were prepared by a potentiostatic hold at various potentials and exposure time.Recent investigation revealed that the localized corrosion mode of the solute-rich Al-Cu-Mg-based amorphous alloys was pitting with localized dealloying of Al and Mg isolated to pits [4]. Oxide breakdown produces…”
mentioning
confidence: 99%
“…Recent investigation revealed that the localized corrosion mode of the solute-rich Al-Cu-Mg-based amorphous alloys was pitting with localized dealloying of Al and Mg isolated to pits [4]. Oxide breakdown produces…”
mentioning
confidence: 99%